Performance Evaluation of GaN based Thin Film Transistor using TCAD Simulation - Shashi Kant Dargar; J K Srivastava; Santosh Bharti; Abha Nyati (International Journal of Electrical and Computer Engineering (IJECE), 2017)
As reported in past decades, gallium nitride as one of the most capable compound semiconductor, GaN-based high-electron mobility transistors are the focus of intense research activities in the area of high power, high-speed, and high-temperature transistors. In this paper we present a design and simulation of the GaN based thin film transistor using sentaurus TCAD for the extracting the electrical performance. The resulting GaN TFTs exhibits good electrical performance in the simulated results, including, a threshold voltage of 12-15 V, an on/off current ratio of 6.5×107 ~8.3×108, and a sub-threshold slope of 0.44V/dec. Sentaurus TCAD simulations is the tool  which offers study of comprehensive behavior of semiconductor structures with ease. The simulation results of the TFT structure based on gallium nitride active channel have great prospective in the next-generation flat-panel display applications.